2009
DOI: 10.1007/s10570-009-9373-2
|View full text |Cite
|
Sign up to set email alerts
|

Elastic coils: deformation micromechanics of coir and celery fibres

Abstract: Natural fibres, such as flax and hemp, are typically chosen as reinforcing elements in composites to replace traditional glass fibres due to their high stiffness, strength and low strain to failure. Some plant fibres such as coir and celery however possess high strains to failure, which could be utilised in a composite to enhance toughness. This paper reports on the use of Raman spectroscopy to follow the molecular deformation of single fibres of coir and celery. The technique is also used to characterise the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 35 publications
2
28
1
Order By: Relevance
“…The Raman band intensity remained approximately constant with rotation angle for both PS/CNC-and PVA/CNC-based composite fibres. Previous research has shown that more ellipsoidal shapes are obtained for these polar plots when orientation of the cellulose occurs, be it in chain form or emanating from CNCs themselves [18,19]. This result suggests a lack of orientation of CNCs in both PS and PVA fibres.…”
Section: Raman Spectroscopic Characterization Of Cnc Orientationmentioning
confidence: 76%
“…The Raman band intensity remained approximately constant with rotation angle for both PS/CNC-and PVA/CNC-based composite fibres. Previous research has shown that more ellipsoidal shapes are obtained for these polar plots when orientation of the cellulose occurs, be it in chain form or emanating from CNCs themselves [18,19]. This result suggests a lack of orientation of CNCs in both PS and PVA fibres.…”
Section: Raman Spectroscopic Characterization Of Cnc Orientationmentioning
confidence: 76%
“…Then, these fibers were dried during 2 days at room temperature followed by oven drying for 2 hours. Coir fibers were manually twisted and then twisted fibers were made as coir fiber mat [2]. Meanwhile, agave fibers were composed manually in mat form.…”
Section: Methodsmentioning
confidence: 99%
“…Coir/glass hybrid composite has been studied by where coir fiber as core and glass fiber as shell, and woven coir and glass fiber [4]. The tensile strength of coir/glass hybrid composite tends to rise if increasing content of glass fiber in the composite [2]. Then, eco-friendly fibers used as reinforcement of hybrid composite are coir/jute fibers [5], coir/oil palm fibers [6], coir/sisal fibers [7], coir/angustifolia Haw agave fibers [8].…”
Section: Introductionmentioning
confidence: 99%
“…coir fiber. Coir fiber was evaluated its mechanical properties by Kulkarni et al [4], Bakri and Eichhorn [5]. Its fiber has been used for reinforcing thermoset or thermoplastic in composite.…”
Section: Introductionmentioning
confidence: 99%